Spatial disparities of antenatal care utilization among pregnant women in sub-Saharan Africa—Bayesian geo-additive modelling approach - Belay, Denekew Bitew; Fenta, Haile Mekonnen; Birhan, Nigussie Adam; Rad, Najmeh Nakhaei; Chen, Ding-Geng (Frontiers in Public Health, 2025)
BackgroundAntenatal care (ANC) is critical for ensuring healthy pregnancies and positive birth outcomes. Despite its importance, significant disparities in ANC access and utilization exist across sub-Saharan Africa (SSA), influenced by various socioeconomic, geographical, and systemic factors. This study aimed to analyze the spatial disparities in the proportion of recommended ANC utilization and its associated risk factors among pregnant women in 34 sub-Saharan African countries.MethodThis study utilized the most recent Demographic and Health Survey (DHS) data from 34 countries across the SSA region. To assess the spatial disparities and their associated risk factors of ANC utilization, a geo-additive model via the Integrated Nested Laplace Approximation (INLA) was adopted.ResultThe overall prevalence of recommended ANC utilization in SSA was 22.15%, with a significant difference between countries, ranging from 0.27% in Rwanda to 76.28% in Zimbabwe. Both Moran’s I and Geary’s C tests, with different neighborhood structures, evidenced the existence of spatial autocorrelation of ANC utilization among women in SSA countries. A Bayesian geo-additive model with Besag-York-Mollié (BYM) mixed effect was found to be the best model to assess the spatial dependencies and the non-linear effects of the factors on ANC utilization among women of reproductive age. The study showed that the existence of spatial disparities in ANC utilization and media exposure, as well as the mother’s work status, partner’s working status, age of mother, age at first cohabitation, and place of delivery, has a significant effect on ANC utilization.ConclusionThe overall coverage of recommended ANC in SSA countries falls short of the global minimum recommended ANC utilization. The lower coverage and inequality of ANC utilizations are influenced by underutilization of healthcare services, economic status, women’s education coverage, poor/absence of transportation facilities, and media exposure related to healthy reproduction. Empowering women through different media outlets, strengthening their economic power, easy access to health facilities, and decision-making power increases maternal healthcare service utilization.